Determinants’ Analysis of the Perception of the Sidewalk as a Public Good in Cotonou - AVOCE VIAGANNOU, FANOUGBO (My University, 2018)
This paper aims to study the determinants of the perception of the sidewalk as a public good in Cotonou. In fact, some economic agents‟ behavior towards the sidewalk leads to think that it is not a public good. To highlight this problem, an estimation of a Logit model has been done over a random sample of 373 agents who work close to sidewalks. Results show that people admit the sidewalk as a public good. In addition, the determinants of the perception of the sidewalk as a public good are: (i) the education level of agents, (ii) the costs of space occupation, and (iii) the fact that they share the sidewalk with pedestrians. The third determinant shows that the non- exclusion is not total and the sidewalk is not a pure public good. For the sidewalk to be a pure public good, an optimal management model should be developed for good use of sidewalks.
Keywords: Logit model; Costs of space occupation; Sidewalk; Public good; Cotonou.